Associations of Ficolins With Hematological Malignancies in Patients Receiving High-Dose Chemotherapy and Autologous Hematopoietic Stem Cell Transplantations - Świerzko, Anna S.; Michalski, Mateusz; Sokołowska, Anna; Nowicki, Mateusz; Szala-Poździej, Agnieszka; Eppa, Łukasz; Mitrus, Iwona; Szmigielska-Kapłon, Anna; Sobczyk-Kruszelnicka, Małgorzata; Michalak, Katarzyna; Gołos, Aleksandra; Wierzbowska, Agnieszka; et al. (Frontiers in Immunology, 2020)
A prospective study of 312 patients [194 with multiple myeloma (MM), 118 with lymphomas (LYMPH)] receiving high-dose chemotherapy and autologous haematopoietic stem cell transplantation (auto-HSCT) was conducted. Ficolins are innate immune defense factors, able to distinguish between „self” „abnormal self” and „non-self” and contribute to elimination of the last two by direct opsonization and/or initiation of complement activation via the lectin pathway Concentrations of ficolin-1, ficolin-2 and ficolin-3 in serially taken serum samples were determined as were polymorphisms of the corresponding (FCN1, FCN2 and FCN3) genes. Serum samples were collected before conditioning chemotherapy, before HSCT, and once weekly post-HSCT (4-5 samples in total); some patients were also sampled at one and/or three months post-transplantation. The control group (C) consisted of 267 healthy unrelated individuals. Median ficolin-1 and ficolin-2 (but not ficolin-3) levels in MM patients’ sera taken before chemotherapy were lower (and correspondingly frequencies of the lowest concentrations were higher) compared with controls. That appeared to be associated with the malignant disease itself rather than with post-HSCT complications (febrile neutropenia, infections accompanied or not with bacteremia). Higher frequencies of the FCN1 genotype G/A-C/C-G/G (corresponding to polymorphisms at positions -542, -144 and +6658, respectively) and FCN2 gene heterozygosity for the -857 C>A polymorphism were found among patients diagnosed with MM, compared with C group. Furthermore, FCN2 G/G homozygosity (-557 A>G) was found more frequently, and heterozygosity G/T at +6424 less frequently, among LYMPH patients than among healthy subjects. Heterozygosity for +1637delC mutation of the FCN3 gene was more common among patients diagnosed with lymphomas who experienced hospital infections. Although no evidence for an association of low ficolin-1 or ficolin-2 with infections during neutropenia following chemotherapy before HSCT was found, we observed a possible protective effect of ficolins during follow-up.